COMPUTER AIDED TOOL SUPPORT (CATS) FOR INFORMATION STRATEGY PLANNING (ISP): GENERATING APPLICATION PORTFOLIO FOR BUSINESS AREA ANALYSIS (Journal of Information and Communication Technology, 2010)
Information Strategy Planning (ISP) is concerned with an organizationâ€™s plan to acquire appropriate â€œIT blueprintâ€ encompassing suitable hardware, software and telecommunication facilities for the utilization of applications required by the business with adequate support structure. The purpose is to determine the enterpriseâ€™s business goals and a high-level overview of the enterprise, its functions, data and information needs. This research builds an ISP engine, i.e. the Computer Aided Tool Support (CATS) that has the capability to generate application portfolios that can support the business strategy of the enterprise. Application portfolio is a major part of the ISP deliverables which can signifi cantly aid in formulating suitable strategies for IT supply and IT support structure. CATS will help to facilitate End-User Computing as a tool not only to ease endusers in planning for their IT adoption, but also to ensure that their IT investment is aligned to business goals and strategies. CATS will be able to help the Small Medium Enterprise (SME) companies and other organizations in their information-systems planning so that they can achieve their missions and objectives in a more effi cient way.